The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21307/acee-2017-058
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Groundwater Quality in the Context of the Exploitation of Small Drinking Water Intakes

Abstract: In this work, attention has been paid to the problem of quality of groundwater, which is the main source of supply of drinking water for rural inhabitants. In particular, the important factors for the groundwater quality in rural areas have been presented. This paper also shows the impact of the quality and quantity of available water resources on the exploitation of chosen small water intakes. Results of research on the quality parameters of groundwater, obtained in 2012÷2016 for selected rural intakes in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Finally, it was concluded that among all tested membranes, the treatment of chemical site effluents at MT membrane would be preferable due to its capacity, lowest fouling affinity and contaminants removal efficiency. The obtained COD removal rates were compared with ones observed by other authors, who applied low pressure-driven membrane filtration to direct or in combination with coagulation raw coke oven wastewater treatment [23,24]. It was found, that COD elimination (27.1%) was in agreement with other results (30% [23] and 11%-40% [24]).…”
Section: Quality Of Permeatesupporting
confidence: 73%
See 1 more Smart Citation
“…Finally, it was concluded that among all tested membranes, the treatment of chemical site effluents at MT membrane would be preferable due to its capacity, lowest fouling affinity and contaminants removal efficiency. The obtained COD removal rates were compared with ones observed by other authors, who applied low pressure-driven membrane filtration to direct or in combination with coagulation raw coke oven wastewater treatment [23,24]. It was found, that COD elimination (27.1%) was in agreement with other results (30% [23] and 11%-40% [24]).…”
Section: Quality Of Permeatesupporting
confidence: 73%
“…Membrane separation has already been tested in treatment of coke oven wastewater at various treatment stages and in the combination with different unit operations. Due to simple operation, ability to remove a wide range of contaminants and satisfactory chemical resistance, membrane processes seem to offer a promising alternative and/ or support to industrial wastewater treatment, including cokemaking industry [21][22][23]. Mielczarek et al [24] tested ultrafiltration (UF) for raw coke oven wastewater treatment, and the process was used as a direct filtration or in the combination with coagulation [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance Helms and Heidt [17] found that up to 6% of NO x (and up to 10% of PM) traffic related emissions in Germany are caused by mobile construction machinery. Under the assumption, that concentrations in the air in a case of emission sources of low height, are proportional to emissions (what is fulfilled roughly in city-centers) and taking into consideration the 48% share of NO x emission from road-transport sector in total [24,25,26,27] (39% road transport + 9% nonroad transport), the share of construction machines in total NO x concentration yields about 3%. The similar calculations made by Millstein and Harley [18], which assigned 11% of NO x (and 14% of total 1-hour NO 2 level in the air in the vicinity of the conducted construction works was not exceeded.…”
Section: Discussion Of Results and Con-clusionsmentioning
confidence: 99%
“…A balanced land structure contributes to increasing the stability and productivity of agro-landscapes and the sustainability of ecosystems in general. The fundamentals of environmental optimization of agrarian nature were first formulated by V. Dokuchaev as the development of norms relative to the areas of arable land, meadows, forest and water [6,[10][11][12][13][14][15]. The decomposition of waste has the greatest impact on soil, underground water resources, and atmosphere.…”
Section: Data Analysis and Main Materi-alsmentioning
confidence: 99%